Corporate Climate Change Reporting: Evidence from Bangladesh - Mofijul Hoq Masum; Nazmul Hassan; Tasnin Jahan (Journal of Accounting and Management Information Systems (JAMIS), 2019)
Research Question: Do the Bangladeshi business entities concern about the extreme climate change vulnerability of the country? How do they deal with the climate change issues in their corporate reporting? Motivation: As per the Climate Change Vulnerability Index 2014, Bangladesh is one of the most vulnerable countries in the world. To cope up this extreme stage not only the government but also all the stakeholders of the country should come forward. This study aims at exploring the attention of business organizations of Bangladesh toward the climate change issues of the country. Idea: When developed nations realized and shared accountability in relation to the adverse effect of climate change, developing nation pay less attention towards the impact of climate change and environmental degradation (Luo et al., 2013; Amran et al., 2014; Jeswani, 2007). Ironically, academic have paid less attention to examine the organizational efforts towards sustainability and environmental safety in the context of developing countries (Kabir & Akinusi, 2012). This research is intended to explore climate change reporting practices in developing countries - Bangladesh. Data: A purposive sampling of 82 companies listed in the Dhaka Stock Exchange (DSE) has been taken based on the year 2016 or 2015-2016. Tools: An un-weighted Climate Change Disclosure Index (CCDI) has been constructed and used to understand the climate change disclosure level practiced by selected companies. Findings: we have found a very poor disclosure levels practiced by the Bangladeshi listed companies as the mean climate change disclosure index (CCDI) is only 3.02 out of the maximum possible score of 28. Surprisingly, heavily polluting industries have very poor climate change disclosure indices compared to the non-polluting industries. Contributions: The study will create awareness to all the stakeholders of the climate change issues so that a holistic approach can be executed not only to accelerate the literatures on climate change but also to ensure sustainability on corporate climate change reporting.
Keywords: Q50; Q54; M1; 650; Climate change disclosures; sustainability reporting; content analysis; listed companies